AN ANALYSIS OF INTROVERT LEARNERS’ NEED ANALYSIS IN ENGLISH SPEAKING ACTIVITY AT SMP-IT HIKMATUL FADHILLAH - Selvy Noer Haiyu; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
The objective of the study was to reveal introvert learners' target needs and learningneeds in English speaking activities. This study was conducted at SMP-IT HikmatulFadhillah, which the sample was twenty introvert learners at grade IX that had beenselected by doing a personality test, which using Eysenck Personality Questionnaire(EPQ). The research method was qualitative descriptive. The data was collected bydistributing the questionnaire and interviewing ten representative introvert learnersand English-speaking teacher. The item questions were adapted from English forSpecific Purposes – A learning Centred Approach by Hutchinson & Waters (1987)and Curriculum Development in Language Teaching by Jack Richards (2001).Theresults revealed that introvert learners need to learn English because they wanted toget a good career in the future, and introvert learners wanted to be able to speakEnglish with their friends at school every day, and so that it can be used as their dailycommunication. As long as they study in their class, the most common problems theyfaced were pronunciation, grammar, and difficulty participating in discussions.Therefore, introvert learners were very interested in learning more aboutpronunciation. Introvert learners need a quiet atmosphere, and they like to study aloneor in pairs. Introvert learners learned easier by listening to something, such aslistening to English songs or podcasts, even in class they were easier to understand bylistening to the teacher's explanation. With these conditions, introverted learners needteachers who can make them more active in class but still comfortable for them.